Crop prices and migration in Viet Nam - Gaia Narciso (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
This paper investigates the effect of commodity prices, in particular rice and coffee, on the individual decision of migrating in Viet Nam. As most coffee production is sold by households for exports, we would expect that coffee price shocks would have a direct effect on the probability of migrating. On the other hand, we would anticipate that fluctuations in rice prices have little or no effect on migration decisions, given that rice is mainly produced for household consumption. The results of the analysis confirm our assumptions. We provide evidence that the lower the coffee price, the higher the likelihood of migrating. This evidence seems to suggest that migration acts as a shock-coping strategy. We find that rice prices have no effect on the probability of migrating. We further explore the extent of migrants' self-selection and show that lower coffee prices increase the migration probability of individuals with lower education.
Keywords: J6; O15; 330; migration; price shocks; Viet Nam